The opioid system as the interface between the brain's cognitive and motivational systems - O'Mara, Shane (Progress in brain research ;, 2018)
"The Opioid System as the Brain's Interface between Cognition and Motivation, Volume 239, focuses on the opioid system as the interface between the brain's cognitive and motivational systems. As the opioid system is widely distributed through the brain, particularly in areas implicated in cognition (hippocampus, prefrontal cortex, claustrum, thalamus) and motivation (hypothalamus, amygdala, pontine nuclei, periaqueductal gray and medulla), this book provides chapters that address ongoing research on topics such as the brain's cognitive system, the brain's motivational system, antidepressant prescription patterns, antidepressant-like effects of opioid receptor modulators, the behavioral effects of antidepressant and anxiolytic drugs, and more"--Publisher's description